Proximate composition and physical properties of steamed sour cassava starch bread - Adegunwa, M.O.; Edema, M.O.; Sanni, Lateef O.; Maziya-Dixon, B.B. (International Association of Hydrological Sciences, 2012)
The effects of steaming (10min, 20min and 30min) on the properties of sour cassava starch bread were evaluated. Properties examined include pH, moisture content, protein, ash, starch, sugar, amylose content and sensory analysis. Amylose content ranged between (14.04-15.73%), Amylopectin ranged between (84.27-85.96 %), protein content ranged between (3.85-4.18%), Starch and Sugar content ranged between (68.07- 69.01%) and (10.12-10.34%) respectively. As the level of steaming increases the fat (11.64-12.59%) and protein content (3.85-4.18%) increases. 10min-steamed bread was adjudged the best for sour cassava starch bread production as its bread had the highest score for overall acceptability (6.0) and other sensory parameters evaluated.